Displacement Solution of Salt Cavern with Shear Dilatation Behavior Based on Hoek-Brown Strength Criterion - Huabin Zhang; Qingqing Zhang; Laigui Wang (Advances in Civil Engineering)
In this study, an analytical solution of stress, strain, and displacement, in the elastic and plastic zone is proposed. The solution is derived on the basis of ideal elastoplastic mechanical model of spherical salt cavern with shear dilatation behavior, by adopting Hoek-Brown (H-B) criterion. The solution obtains not only in small and large strain stage but also in creep stage. The proposed solution is validated, by comparison of the obtained results with numerical results in FLAC3D. The results indicate that the result obtained adopting the H-B criterion is closer to that one obtained adopting the Mohr-Coulomb (M-C). The H-B criterion is more applicable for the salt cavern construction as it considers the structural characteristics of the rock salt formation. The displacement difference obtained by two different methods decreases with the increase of GSI or running pressure, but it increases with the enlarged angle of dilation. The influence of different assumptions of elastic strain of plastic zone on displacements is more significant under large strain conditions. The influence of the angle of dilation on displacements is more obvious when the elastic strain of plastic zone is given to stationary values, and the influence degree increases with the enlarged angle of dilation. Under the same conditions, the creep displacement decreases with the increase of GSI, and both the creep displacement and the effect degree enhance with the enlarged dilation angle. The proposed solutions can be used in the stability analysis of surrounding rock in the construction and operation of salt cavern storage.